Pengaruh Bimbingan Klasikal dan Layanan Informasi terhadap Peningkatan Karakter Jujur Siswa - Laoli, Erni; Lase, Famahato; Damanik, Hosianna Rodearni; Lase, Justin Foera-era (Indo-MathEdu Intellectuals Journal, 2026)
This study was motivated by the low level of students’ honesty character, reflected in behaviors such as cheating, lying, and denying mistakes at SMK Negeri 3 Hiliserangkai. The research aimed to analyze the effect of classical guidance services and information services on improving students’ honesty character, both simultaneously and partially. A quantitative associative approach was employed using multiple linear regression analysis. The population consisted of 190 students, with a purposive sample of 30 eleventh-grade TKJ students. Data were collected through a closed-ended questionnaire that had been tested for validity and reliability, and were analyzed using prerequisite tests and regression hypothesis testing. The findings revealed that classical guidance and information services had a significant effect on enhancing students’ honesty character, both jointly and individually. Improvement was indicated by the difference in scores before and after the intervention. These results confirm that structured guidance and counseling interventions are effective in strengthening the internalization of honesty values and contribute significantly to the reinforcement of character education in schools.